The Structural Model of Death Anxiety and Self-Acceptance Based on Differentiation with the Mediating Role of Self-Compassion in the Elderly - Kia, Behdokht; Tizdast, Taher; Eslahi Farshami, Fatemeh (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to determine the fit of a structural model of death anxiety and self-acceptance based on psychological flexibility and differentiation, with the mediating role of self-compassion in the elderly.Methods and Materials: The research method was fundamental, descriptive, and correlational in nature. The statistical population consisted of all individuals aged 60 years and above residing in daily elderly care centers in Nowshahr and Chalous counties from February 2024 to August 2024 (N = 232). Due to the limited size of the population, a census method was used, and research questionnaires were distributed to all members of the population. Ultimately, due to damaged or incomplete questionnaires, data from 215 questionnaires were analyzed (n = 215). The research instruments included the Templer Death Anxiety Scale (1970), the Unconditional Self-Acceptance Questionnaire by Chamberlain and Haaga (2001), the Acceptance and Action Questionnaire-II (Bond et al., 2007), the Differentiation of Self Inventory by Skowron and Friedlander (1998), and Neff’s Self-Compassion Scale (2003). Data analysis was conducted using SPSS version 26 and LISREL 8 software.Findings: Pearson correlation analysis indicated a positive and significant relationship between differentiation and self-compassion (r = 0.645, p < .01); a negative and significant relationship between differentiation and death anxiety (r = -0.411, p < .01); a positive and significant relationship between differentiation and self-acceptance (r = 0.700, p < .01); a negative and significant relationship between self-compassion and death anxiety (r = -0.352, p < .01); and a positive and significant relationship between self-compassion and self-acceptance (r = 0.846, p < .01). Path analysis revealed that the indirect path from differentiation to death anxiety through the mediating role of self-compassion was statistically significant (β = -0.629, p < .01). Furthermore, the indirect path from differentiation to self-acceptance through self-compassion was also statistically significant (β = 0.861, p < .01).Conclusion: Thus, the structural model of death anxiety and self-acceptance based on differentiation with the mediating role of self-compassion demonstrated a good fit among elderly individuals residing in daily care centers in Nowshahr and Chalous. These findings may serve as a basis for developing comprehensive therapeutic models to enhance psychological well-being among the elderly.Keywords: Death Anxiety, Self-Acceptance, Differentiation, Self-Compassion, Elderly.